Inspections on board oil tankers : present situation and suggestion for improvement - Grbić, Luka (Array, 2018)
Oil tanker inspections have an important role in enhancing safety and minimizing the risk of oil pollution. However, research has indicated that inspection items are overlapping among inspection regimes observed in a given time span on board oil tankers, thus making negative impact on ship safety, unnecessarily consuming shipboard human resources and having adverse economic effects. In this paper, current inspections performed on board oil tankers have been presented, including duration, intensity and average costs, directly or indirectly paid by shipowners. Our analysis of surveyed components by all regimes has showed that it is possible to reduce critical inspection parameters without compromising safety by introducing a unified inspection method. A content of such inspection, consisting of 529 components, has been presented. Performing the proposed inspection method and sharing its results among interested parties of oil tanker safety regime has been suggested as a measure that could improve oil tanker safety and pollution prevention.